Current Opinion and Practice on Peritoneal Carcinomatosis Management: The North African Perspective - Souadka, Amine; Essangri, Hajar; Makni, Amin; Abid, Mourad; Ayadi, Mouna; Ksantini, Feriel; Kordjani, Zakia; Ballah, Yousri; Bouka, Jemila; Benkabbou, Amine; Majbar, Mohammed Anass; El Khannoussi, Basma; et al. (Frontiers in Surgery, 2022)
Background : The status of peritoneal surface malignancy(PSM) management in north Africa is undetermined. The aim of this study was to assess and compare current practice and knowledge regarding PSM and examine satisfaction with available treatment options and need for alternative therapies in North Africa. Methods: This is a qualitative study involving specialists participating in PSM management in north Africa. The survey analysed demographic characteristics and current knowledge and opinions regarding PSM management in different institutions. We also looked at goals and priorities, satisfaction with treatment modalities and heated intraperitoneal chemotherapy(HIPEC) usefulness according to specialty, country, years of experience and activity sector. Results : 103participants responded to the survey (response rate of 57%), including oncologists and surgeons. 59.2% of respondents had more than 10 years experience and 45.6% treated 20 to 50PSM cases annually. Participants satisfaction with PSM treatment modalities was mild for gastric cancer (3/10[IQR 2–3]) and moderate for colorectal (5/10[IQR 3–5]), ovarian (5/10[IQR 3–5]) and pseudomyxoma peritonei (5/10[IQR 3–5]) type of malignancies. Good quality of life and symptom relief were rated as main priorities for treatment and the need for new treatment modalities was rated 9/10,[IQR 8–9]. The perceived usefulness of systemic chemotherapy in first intention was described as high by 42.7% and 39.8% of respondents for PSM of colorectal and gastric origins, while HIPEC was described as highly useful for ovarian (49.5%) and PMP (73.8) malignancies. Conclusions : The management of PSM in the north African region has distinct differences in knowledge, treatments availability and priorities. Disparities are also noted according to specialty, country, years of expertise and activity sector. The creation of referral structures and PSM networks could be a step forward to standardized PSM management in the region.